2016
DOI: 10.1039/c6ra06075g
|View full text |Cite
|
Sign up to set email alerts
|

Selective homodimerization of unprotected peptides using hybrid hydroxydimethylsilane derivatives

Abstract: A straightforward way to dimerize unprotected peptide sequences is presented; it relies on a chemoselective condensation of hybrid peptides bearing a hydroxydimethylsilyl group at a chosen position to generate siloxane bonds upon freeze-drying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Compound 4 was dissolved in water (1/1000 TFA)/ethanol, 30/5, v/v solution at a 30 × 10 −3 m concentration. Noteworthy we demonstrated that dimethylhydroxysilane peptides did not form dimers through intermolecular reaction in acidic solutions . Pieces of catheters were activated by oxygen plasma and immediately incubated in this solution at 60 °C for 12 h. As a control experiment, pieces of catheters were also incubated in a solution of the unsilylated fluorescein derivative 3 .…”
Section: Antibacterial Hybrid Peptidementioning
confidence: 94%
See 1 more Smart Citation
“…Compound 4 was dissolved in water (1/1000 TFA)/ethanol, 30/5, v/v solution at a 30 × 10 −3 m concentration. Noteworthy we demonstrated that dimethylhydroxysilane peptides did not form dimers through intermolecular reaction in acidic solutions . Pieces of catheters were activated by oxygen plasma and immediately incubated in this solution at 60 °C for 12 h. As a control experiment, pieces of catheters were also incubated in a solution of the unsilylated fluorescein derivative 3 .…”
Section: Antibacterial Hybrid Peptidementioning
confidence: 94%
“…Several chlorodimethylsilylated peptides were already prepared by our group as precursors for G protein‐coupled receptor (GPCR) ligand dimers. These peptide may undergo dimerization upon freeze drying or precipitation but are only observed in monomeric form when treated in acidic conditions, enabling their purification by classical RP HPLC in water/acetonitrile (with TFA, 1/1000, v/v) solvent system. The hybrid peptide 2 “ready to use” was purified and characterized (See the Supporting Information).…”
Section: Antibacterial Hybrid Peptidementioning
confidence: 99%
“…Other examples of silylated peptides include peptides with biological activity (anti-angiogenic, ( Ciccione et al, 2016 ; Maurel et al, 2021 ), regulatory, ( Jebors et al, 2015 ; Echalier et al, 2016b ), antibacterial ( Masurier et al, 2018 )), catalytic activity ( Jebors et al, 2013b ) or enzyme-responsive degradation. ( Maggini et al, 2016 ).…”
Section: Bioink Silylated Componentsmentioning
confidence: 99%